Socioeconomic Factors Associated With Glycemic Measurement and Poor HbA1c Control in People With Type 2 Diabetes: The Global DISCOVER Study - Gomes, Marília B.; Tang, Fengming; Chen, Hungta; Cid-Ruzafa, Javier; Fenici, Peter; Khunti, Kamlesh; Rathmann, Wolfgang; Shestakova, Marina V.; Surmont, Filip; Watada, Hirotaka; Medina, Jesús; Shimomura, Iichiro; et al. (Frontiers in Endocrinology, 2022)
DISCOVER is a 3-year observational study program of 15,983 people with type 2 diabetes initiating second-line glucose-lowering therapy in 38 countries. We investigated the association between socioeconomic status and both the availability of a baseline glycated hemoglobin (HbA1c) measurement and poor glycemic control (HbA1c level ≥ 9.0%) in participants enrolled in DISCOVER. Factors associated with a lack of baseline HbA1c measurement or an HbA1c level ≥ 9.0% were assessed using three-level hierarchical logistic models. Overall, 19.1% of did not have a baseline HbA1c measurement recorded. Low country income and low educational level were independently associated with having a missing baseline HbA1c measurement. Of the participants with an available HbA1c measurement, 26.9% had a HbA1c level ≥ 9.0%; 68.7% of these individuals were from lower- or upper-middle-income countries. Factors associated with an increased likelihood of poor glycemic control included low country income, treatment at a site with public and/or governmental funding (vs. private funding) and having public or no health insurance (vs. private). A substantial proportion of DISCOVER participants did not have an HbA1c measurement; more than one-quarter of these participants have poorly controlled type 2 diabetes. Both individual- and country-level socioeconomic factors affect the quality of care regarding glycemic control.